The Effect of Work Motivation, Transformational Leadership, and Organizational Communication on Employee Performance at Gumuh Sari Rekreasi Bali - I Wayan Rahul Suputra rahul; I Gusti Ngurah Widya Hadi Saputra (Journal of Innovative and Creativity (Joecy), 2026)
The study purpose was to analyze the effects of work motivation, transformational leadership, and organizational communication on employee performance at Gumuh Sari Rekreasi Bali, a recreation business whose operations depend on intensive employee-customer interaction and consistent service delivery. Materials and methods. The study used a quantitative associative design. The population consisted of all 107 employees and a saturated sampling technique was applied, so the entire population became the sample. Data were collected through a five-point Likert questionnaire and analyzed using SPSS. Instrument testing included Pearson correlation validity and Cronbach's alpha reliability tests. The analysis continued with normality, multicollinearity, and heteroskedasticity tests, multiple linear regression, partial t-tests, a simultaneous F-test, and the coefficient of determination. Results. Work motivation had a positive and significant effect on employee performance (B = 0.938; t = 13.887; p < 0.001), and transformational leadership also had a positive and significant effect (B = 0.319; t = 4.996; p < 0.001). Organizational communication had a negative and significant partial effect after the other predictors were controlled (B = -0.264; t = -4.220; p < 0.001). Simultaneously, the three predictors significantly affected performance (F = 263.508; p < 0.001). The adjusted R-squared value was 0.881. Conclusions. Employee performance at Gumuh Sari Rekreasi Bali is strongly associated with motivational and organizational resources. Management should strengthen employee motivation and transformational leadership while improving the clarity, relevance, structure, channel, and timing of organizational communication rather than simply increasing communication frequency.